Intestinal parasitic infection among the HIV-infected patients in Nepal - Tiwari, Bishnu Raj; Ghimire, Prakash; Malla, Sarala; Sharma, Bimala; Karki, Surendra (The Journal of Infection in Developing Countries, 2013)
Introduction: Intestinal parasitic infection has been a significant problem in HIV patients, worldwide. In this study, we aimed to measure the prevalence and identify the factors associated with intestinal parasitic infection in people infected with HIV and attending National Public Health Laboratory in Kathmandu, Nepal, for CD4 T-cell count. Methodology: An analytical cross-sectional study in 745 HIV-infected people attending for CD4 T-cell count was conducted. Results: The prevalence of intestinal parasitic infection was 22.4% (95% CI 19.5 to 25.5). In univariate analysis, age, sex, longer time since diagnosis of HIV, CD4 T-cell count of <200/µL, diarrhoea, marital status, and being under tuberculosis (TB) treatment were significantly associated with increased odds of intestinal parasite infection. However, in the logistic regression model, only the CD4 T-cell count of <200/µL (adjusted OR=4.2, 95% CI 2.5 to 7.0), diarrhoea (adjusted OR=2.8, 95% CI 1.8 to 4.3) and being under TB treatment (adjusted OR=2.9, 95% CI 1.8 to 4.6) remained as significant predictors. On stratification, CD4 T-cell count of <200/ µL was independently associated with higher odds of protozoal as well as helminthes infection. The parasites Cryptosporidium and Cyclospora were observed only in participants with CD4 T-cell counts <200/µL. Conclusions: Both protozoal and helminthic intestinal parasitic infections are common in HIV-infected people seeking care in healthcare facilities. The poor immune status as indicated by low CD4 T-cell count and TB may account for such a high risk of parasitic infection.